La expresión corporal en el desarrollo dinámico en los niños del 1er año paralelo “B”, de la Unidad Educativa “San Andrés”, del Cantón Guano, Provincia Chimborazo período 2015- 2016. - Guilcapi Alvarado, Margarita Rocío (2016)
This research was conducted with children five to six years of the Education Unit “San Andres” is of great interest bodily expression in the dynamic development in children to help improve their psychomotor, cognitive, socio-emotional skills, their skills to socialize and integrate with other people, through constant practice of activities performed by the body as play, dance, sing, dance, visual arts, designed to develop their creative language, and expressive. According to the objectives identified what level of knowledge possessed by teachers as it relates to body language and dynamic development, it was determined that methodology used, and how they influence these strategies for the development of the child, research method used was inductive, deductive, analytical and synthetic, the type of research that was applied was the explanatory field, bibliographic and documentary, to collect data and information, such as observation technique was used. After some findings diagnosis was identified as it became clear that the highest percentage of children having difficulties in expressing themselves, communicate and interact with other children. In conclusion of this work was identified that most educators have knowledge about body language but about the dynamic development their notions are very few, it was determined that basic techniques of body expression practiced because the movements of the children were monotonous and watched difficulty maintaining his posture, balance, coordination, control and precision in their movements, affecting the development of their cognitive abilities, psychomotor and affective. We recommend train educators in practice on activities and techniques that can be used as an educational resource, as used herein as material support and consultation to have a better approach to this issue.